INTELLECTUAL CAPITAL IN THELITERATURE FROM 2020 TO 2024 - Molina Gonzalez, Maria del Rosario (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The pandemic, in the educational field, was attacked byanti-COVID-19 policies that focused their attention on the confinement of distancing of people in order to move towards the virtual classroom. The impact of distance and asynchronous training strategies on the formation of intellectual capital is the objective of this paper. A documentary, cross-sectional and exploratory study was carried out with a selection of sources indexed to international repositories, considering a search by keywords in the period from 2020to2024. A structure of networks was found that were configured based on their proximity between nodes and edges. The findings were discussed in relation to the consulted literature,recommending theextension of the data.